2021
DOI: 10.3390/catal11121522
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a Fixed Bed Reactor Model for Dimethyl Ether Synthesis Using Pilot-Scale Plant Data

Abstract: The one-dimensional (1D) mathematical model of fixed bed reactor was developed for dimethyl ether (DME) synthesis at pilot-scale (capacity: 25–28 Nm3/h of syngas). The reaction rate, heat, and mass transfer equations were correlated with the effectiveness factor. The simulation results, including the temperature profile, CO conversion, DME selectivity, and DME yield of the outlet, were validated with experimental data. The average error ratios were below 9.3%, 8.1%, 7.8%, and 3.5% for the temperature of the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 39 publications
(44 reference statements)
1
4
0
Order By: Relevance
“…Therefore, in STD synthesis, consideration of H 2 /CO ratios above 1 can ensure improved syngas conversion rates. As also evident in the work of Song et al, 36 increasing the ratio to 1.3 leads to an increase in the CO conversion and DME yield. Also, other authors 15,37−40 have experimentally found that the H 2 /CO ratios up to 2 enhance the conversion rate when the feed contains CO 2 in addition to H 2 and CO.…”
Section: Theoretical Background and Considerationssupporting
confidence: 67%
See 2 more Smart Citations
“…Therefore, in STD synthesis, consideration of H 2 /CO ratios above 1 can ensure improved syngas conversion rates. As also evident in the work of Song et al, 36 increasing the ratio to 1.3 leads to an increase in the CO conversion and DME yield. Also, other authors 15,37−40 have experimentally found that the H 2 /CO ratios up to 2 enhance the conversion rate when the feed contains CO 2 in addition to H 2 and CO.…”
Section: Theoretical Background and Considerationssupporting
confidence: 67%
“…In STD synthesis, keeping low concentrations of CO 2 in the feed at 4–6 mol % has a positive impact on DME productivity; however, higher amounts reduce CO conversion due to the influence on the WGS reaction . Besides, it has been reported that the presence of CO 2 in the feed reduces the maximum temperature in the reactor bed, thereby ensuring a safer operation . Here, the CO 2 mole fraction was adjusted within a range of 7.0–7.5 and 6.0–6.5% in the STM and STD reactors, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, scale-up is conducted by multiple tubes arranged in parallel (multitubular reactor) with an external cooling facility. 176,177 Still, it has the advantage of working in the adiabatic regime. Farsi et al have modeled isothermal and adiabatic reactors to establish a reducing temperature profile for the methanol to DME process.…”
Section: Catalysis Science and Technology Reviewmentioning
confidence: 99%
“…In order to further enhance temperature control, the isothermal packed bed reactor with external cooling was also proposed. The catalyst is positioned in a vertical tubes or shell surrounded by saturated water [28]. The heat from exothermic reaction is eliminated using saturated water and steam generated.…”
Section: Fixed Bed/packed Bed Reactormentioning
confidence: 99%